Inorganic-organic hybrid sorbent for aromatic desulfurization of hydrocarbons: Regenerative adsorption based on a charge-transfer complex - Armaghan, M.; Amini, M.M.; Khavasi, H.R.; Zhang, W.H.; Ng, S.W. (Royal Society of Chemistry, 2016)
A new series of inorganic-organic hybrid materials as sorbents for the adsorption of dibenzothiophene (DBT) and 4,6-dimethyldibenzothiophene (4,6-DMDBT) have been prepared by functionalizing mesoporous silica with 9,10-anthraquinone derivatives. A selected sorbent was fully characterized via13C and 29Si cross-polarization magic-angle solid-state nuclear magnetic resonance (CP-MAS NMR), FTIR spectroscopy, powder X-ray diffraction (PXRD) and thermal analysis (TGA-DTA). The prepared materials were used to adsorb DBT and 4,6-DMDBT from C7 hydrocarbons under ambient conditions. The results show that the hybrid material prepared by the functionalization of mesoporous silica with 9,10-dioxo-5-((3-(triethoxysilyl)-propyl)amino)-1,5-dichloro-4,8-dinitroanthraquinone is an efficient and regenerable sorbent for adsorption of DBT and 4,6-DMDBT by π-π interaction. To demonstrate the adsorption of DBT and 4,6-DMDBT through π-π interaction, a charge-transfer complex (CTC) of 1,5-dichloro-4,8-dinitroanthraquinone and 4,6-DMDBT was prepared and characterized by FT-IR, 1H and 13C NMR spectroscopy, MS, TGA-DTA and single-crystal X-ray diffraction. The results show that 1,5-dichloro-4,8-dinitroanthraquinone produces a CTC with 4,6-DMDBT, and when it is grafted on Si-MCM-41, it produces a hybrid material with the capability of adsorbing only aromatic DBT and 4,6-DMDBT rather than anthracene, naphthalene and xylene. In contrast, 1,5-dichloroanthraquinone and 1,5-dicyanoanthraquinone neither produce a CTC nor adsorb DBT, 4,6-DMDBT, anthracene, naphthalene and xylene after they are grafted on Si-MCM-41. This study proves that the hybrid material prepared from mesoporous silica and 9,10-dioxo-5-((3-(triethoxysilyl)-propyl)amino)-1,5-dichloro-4,8-dinitroanthraquinone is an efficient, environmentally benign and regenerable sorbent for the removal of DBT and 4,6-DMDBT from C7 hydrocarbons.